Bunny$1 (Bs noisy book s - Brown, Margaret Wise, 1910-1952.; McCue, Lisa (New York : Hyperion Books, 2000)
A little bunny listens to noises all around him and then makes some of his own.
Keywords: Rabbits -- Fiction; Sound -- Fiction